2022
DOI: 10.1021/acsami.1c22092
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Bifunctional Electrodes Based on Amorphous Co–Ni–S Nanoflake Arrays with Atomic Dispersity of Active Sites for Overall Water Splitting

Abstract: Fabrication of amorphous electrocatalysts without noble metals for cost-effective full water splitting is highly desired but remains a substantial challenge. In the present work, we report a facile strategy for exploring integrated bifunctional electrocatalysts based on amorphous cobalt/nickel sulfide nanoflake arrays self-supported on carbon cloth, by tailoring competitive coordination of metal ions between glucose and 2-aminoterephthalic acid. Ultrahigh dispersion of binary metal active sites with balanced a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 71 publications
(113 reference statements)
0
26
0
Order By: Relevance
“…The frequent occurrence of climate change and resource shortages have drawn widespread attention to hydrogen energy as a clean and sustainable source. Among the existing hydrogen production technologies, electrocatalytic hydrogen evolution reaction (HER) stands out in terms of being convenient, environmentally friendly, and highly efficient. The most widely accepted electrocatalysts are platinum, , rubidium, , rhodium, and iridium owing to their low overpotentials, Tafel slopes, and good stability. The application of precious metals as electrocatalysts is restricted by their high cost and scarcity of elements. In light of this fact, nonprecious metal catalysts have been extensively investigated. A number of catalysts with excellent performance have been proposed, including phosphides, sulfides, oxides, hydroxides, , carbides, , and so on, which are expected to be promising substitutes for precious metal electrocatalysts due to their low cost and simple preparation methods. …”
Section: Introductionmentioning
confidence: 99%
“…The frequent occurrence of climate change and resource shortages have drawn widespread attention to hydrogen energy as a clean and sustainable source. Among the existing hydrogen production technologies, electrocatalytic hydrogen evolution reaction (HER) stands out in terms of being convenient, environmentally friendly, and highly efficient. The most widely accepted electrocatalysts are platinum, , rubidium, , rhodium, and iridium owing to their low overpotentials, Tafel slopes, and good stability. The application of precious metals as electrocatalysts is restricted by their high cost and scarcity of elements. In light of this fact, nonprecious metal catalysts have been extensively investigated. A number of catalysts with excellent performance have been proposed, including phosphides, sulfides, oxides, hydroxides, , carbides, , and so on, which are expected to be promising substitutes for precious metal electrocatalysts due to their low cost and simple preparation methods. …”
Section: Introductionmentioning
confidence: 99%
“…Table 1 shows the summary of HER and OER activity of some typical electrocatalysts reported in the literatures. Obviously, the HER and OER catalytic performance of NiCo 2 O 4 -2KCl is comparable to that of the recently-developed HER/OER bifunctional catalysts, although the highly conductive substrates were not applied to support as the binder-free electrodes, such as carbon cloth ( Dong et al, 2022 ), Ni foams ( Ha et al, 2019 ; Du et al, 2021 ; He et al, 2021 ), etc.…”
Section: Resultsmentioning
confidence: 96%
“…However, they are limited in large-scale production due to high costs and low reserves. In recent years, various Co-based electrocatalysts, such as phosphides (Zhang et al, 2022b), carbides (Wang et al, 2021), oxides (Jung et al, 2021) and sulfides (Dong et al, 2022) have been developed and applied for water splitting to hydrogen. Among them, NiCo 2 O 4 spinel oxide has shown great application potentials in many energy storage and conversion systems (Chen et al, 2018;Ranjani et al, 2018), because of simple preparation methods, high stability against corrosion in electrochemical systems, and, more importantly, high electrochemical activity (Ha et al, 2019;Du et al, 2021;Sun et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Combining the structural advantages of crystalline and amorphous catalysts to design crystalline–amorphous heterostructure catalysts could retain their inherent properties. Such materials can provide more defects as unsaturated active sites to show better activity compared with crystalline catalysts. , Besides, this novel structure with strong interface interactions would cause charge redistribution to optimize the electron structure. , Wu and Li et al , pointed out that the crystalline–amorphous heterostructure catalysts exhibit high activity by optimizing H atom desorption and H 2 O adsorption, which is confirmed by density functional theory (DFT) calculation. Huang et al reported that the crystalline–amorphous interfaces can provide more active sites, accompanied by boosting the absorption of urea molecules and breaking the chemical bonds to enhance the UOR activity.…”
Section: Introductionmentioning
confidence: 91%